PERANCANGAN SISTEM PERANCANGAN SISTEM INFORMASI PEMASARAN BERBASIS DIGITAL PADA HOME INDUSTRY JAJANAN TRADISIOANAL: Information Systems, Marketing, Digital, Website. - ABRYANDOKO, EKO WAHYU; Prasetyo, Eko (Exact Papers in Compilation (EPiC), 2020)
Pak Dicky's traditional snacks home industry is a UKM engaged in selling traditional culinary snacks which is also well-known by the name of market snacks. In increasing marketing and sales of products to consumers, it is necessary to implement a surefire business strategy to increase new market share. The problem experienced by Pak Dicky's traditional snacks home industry is the limited resources and time in serving every customer / consumer needs. Marketing information system design uses information systems modeling context diagrams, data flowchart diagrams, entity relationship diagran, and e-commerce website design applications by designing fast and appropriate information systems to customers, providing convenience for potential customers, and providing site-based applications web e-commerce that is easy to use by customers based on the design of marketing information systems capable of managing such as making reservations online, providing discounts and promos via the website and searching for product data using the results of application-based marketing information systems e-commerce website is able to provide options / options buying and selling transactions to consumers so that data management is more effective and the presentation of information is fast and flexible. This marketing information system was created using Visual Studio Code as a code editor and database using phpMyAdmin and MySQLi.